Effectiveness of Virtual Bronchoscopy in Evaluation of Centrally Located Lung Cancer - Dilek Hacer ÇEŞME (Bezmiâlem Science, 2021)

(untitled)
Objective:The aim of this study was to compare virtual bronchoscopy (VB) with multi-slice CT (MSCT) in the diagnosis of centrally located lung cancer and to investigate the effectiveness of VB in the diagnosis of the radiologist.Methods:These patients had central lung mass detected during thorax tomography and were diagnosed as having centrally located lung cancer by histopathological examination. Detection and localization of lesions were determined by MSCT and VB. In addition, the evaluation time was determined in seconds with an electronic stopwatch.Results:The mean age of 32 patients included in the study was 58.14±15.09. Centrally located squamous cell carcinoma (n=19) and small cell carcinoma (n=13) were included. Eighteen (54.8%) patients were male and 14 (47.6%) were female. All patients diagnosed as having centrally located lung cancer detected by MSCT were also detected by VB (100%). In the evaluation of patients with MSCT and VB; obstruction and/or lesion and their localization completely overlapped. The mean duration of MSCT evaluation of the patients was determined as 58.7 sec, and the mean duration of VB assessment was 549.9 sec. The mean VB evaluation duration was found to be statistically significantly longer than the mean MSCT evaluation duration.Conclusion:Virtual bronchoscopy does not provide a significant additional contribution to MSCT in the diagnosis of centrally located malignant lung tumor. We think that using VB for diagnosis and navigation will be important in terms of efficiency especially in selected patients due to its low specificity and high sensitivity.